Designing Mesh Turbomachinery with the Development of Euler’s Ideas and Investigating Flow Distribution Characteristics - Yuri Appolonievich Sazonov; Mikhail A. Mokhov; Inna Vladimirovna Gryaznova; Victoria Vasilievna Voronova; Khoren Arturovich Tumanyan; Mikhail Alexandrovich Frankov; Nikolay Nikolaevich Balaka (Salehan Institute of Higher Education, 2022)
This research discusses developing an Euler turbine-based hybrid mesh turbomachinery. Within the framework of mechanical engineering science, turbomachinery classification and a novel method for mesh turbomachinery design were considered. In such a turbomachine, large blades are replaced by a set of smaller blades, which are interconnected to form flow channels in a mesh structure. Previous studies (and reasoning within the framework of inductive and deductive logic) showed that the jet mesh control system allows for operation with several flows simultaneously and provides a pulsed flow regime in flow channels. This provides new opportunities for expanding the control range and reducing the thermal load on the turbomachine blades. The novel method for performance evaluation was confirmed by the calculation: the possibility of implementing pulsed cooling of blades periodically washed by a hot working gas flow (at a temperature of 1000°C) and a cold gas flow (at a temperature of 20°C) was shown. The temperature of the blade walls remained 490–525°C. New results of ongoing research are focused on creating multi-mode turbomachinery that operates in complicated conditions, e.g., in offshore gas fields. Gas energy is lost and dissipated in the throttle at the mouth of each high-pressure well. Within the framework of ongoing research, the environmentally friendly net reservoir energy of high-pressure well gas should be rationally used for operating a booster compressor station. Here, the energy consumption from an external power source can be reduced by 50%, according to preliminary estimates. Doi: 10.28991/CEJ-2022-08-11-017 Full Text: PDF